2011
DOI: 10.1111/j.1468-3083.2010.03763.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunophenotyping of inflammatory cells in subacute prurigo

Abstract: We observed that the inflammatory cell infiltrate in SP mainly consists of T lymphocytes, particularly CD8+ cells, CD15+ neutrophils, and CD68+ macrophages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…PN had been considered to be a variation of eczema, while other conditions such as internal malignancies have been reported to be associated with PN 1 2 . We found that macrophages with an M2 phenotype expressing CD163 represented the majority of cells in the lesional skin, as a previous report described that major cellular components of prurigo lesions are CD68(+) macrophages 3 . We also found that IL-17-positive cells were predominant in vessels of the papillary dermis in the lesional skin with nuclear translocation of phospho-STAT3 in epidermal keratinocytes ( Fig.…”
supporting
confidence: 86%
“…PN had been considered to be a variation of eczema, while other conditions such as internal malignancies have been reported to be associated with PN 1 2 . We found that macrophages with an M2 phenotype expressing CD163 represented the majority of cells in the lesional skin, as a previous report described that major cellular components of prurigo lesions are CD68(+) macrophages 3 . We also found that IL-17-positive cells were predominant in vessels of the papillary dermis in the lesional skin with nuclear translocation of phospho-STAT3 in epidermal keratinocytes ( Fig.…”
supporting
confidence: 86%
“…In a previous study we performed histological investigations of specimens from 136 PN patients and did not find signs of granulomatous inflammation as found in mycobacteriosis 29 . Another group focusing on the inflammatory infiltrate in subacute prurigo also failed to find granulomatous inflammation 30 . This might be due to a selection bias in patient recruitment in our and in the previous studies which leads to detection of different underlying diseases.…”
Section: Discussionmentioning
confidence: 49%
“…29 Another group focusing on the inflammatory infiltrate in subacute prurigo also failed to find granulomatous inflammation. 30 This might be due to a selection bias in patient recruitment in our and in the previous studies which leads to detection of different underlying diseases. For example, in our study, the mean age of patients was 61.5 years while in the study of Rowland Payne et al 10 it was 39.5 years.…”
Section: Discussionmentioning
confidence: 77%
“…Original descriptions of prurigo simplex underline the occurrence of an intraepidermal sero-haemorrhagic vesicle, or crust and infiltration of lymphocytes, with a few histiocytes and eosinophils in the papillary dermis ( 1 ). Histological features common to all cases described in the current study include a mixed superficial and deep perivascular infiltrate of mononuclear cells with scattered interstitial eosinophils ( 9 , 10 , 12 15 ). According to Gamblicher et al ( 15 ), the inflammatory cell infiltrates observed in prurigo simplex appear to be different from those found in eczematous skin changes, e.g.…”
Section: Resultsmentioning
confidence: 58%